2002
DOI: 10.1017/s0954102002000123
|View full text |Cite
|
Sign up to set email alerts
|

Surface and subsurface flows of nutrients in natural and human impacted lake catchments on Broknes, Larsemann Hills, Antarctica

Abstract: Abstract:This study aimed to use nutrients in lake inflows as proxies for assessing human impact and separating this from natural transformations of material in the soil active layer. Nutrients, conductivity and δ 18 O were monitored in surface and subsurface (using ceramic tipped piezometers) lake inflows during summer in near natural and human impacted catchments. The nutrient levels were highly variable but generally higher during the last weeks of the flow, in both subsurface waters and in human impacted c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Besides, one study recently assessed the influence of tourism on surface-water quality and reported that activities related to tourism in a river resulted in higher concentrations of TN and TP in the midstream and downstream areas than upstream [12]. Although natural processes may contribute to increased nutrient levels within aquatic systems [58], the moderate-and high-anthropogenic-disturbance lakes involved in our study indicated that anthropogenically derived sources were responsible for a significant proportion of total nutrient input. The high-anthropogenic-disturbance lakes in our study may be suffering from considerably serious environmental degradation.…”
Section: Water Chemistry Characteristics Under Anthropogenic Disturbancementioning
confidence: 62%
“…Besides, one study recently assessed the influence of tourism on surface-water quality and reported that activities related to tourism in a river resulted in higher concentrations of TN and TP in the midstream and downstream areas than upstream [12]. Although natural processes may contribute to increased nutrient levels within aquatic systems [58], the moderate-and high-anthropogenic-disturbance lakes involved in our study indicated that anthropogenically derived sources were responsible for a significant proportion of total nutrient input. The high-anthropogenic-disturbance lakes in our study may be suffering from considerably serious environmental degradation.…”
Section: Water Chemistry Characteristics Under Anthropogenic Disturbancementioning
confidence: 62%
“…For SIM (figure 4c), highest percentages are visible in the surface layers associated with the recent seasonal decrease in sea-ice extent (approx. stations [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]. This reaches a maximum of 1.8% at station 84, equivalent to 0.8 m of sea-ice derived freshwater in an 85 m thick Surface Water (neutral density γ n < 27.55) layer.…”
Section: Resultsmentioning
confidence: 99%
“…The lake is brackish, covered with ice for 10 months of the year and seasonally stratified (Kaup & Burgess, 2002). The lake becomes completely anoxic during winter, but oxygenated after ice melt out during summer mixing (Kaup & Burgess, 2002), while conductivity is considerably higher than other Larsemann Hills lakes (9160 μ S cm −1 cf. <4200 μ S cm −1 ) (Hodgson et al.…”
Section: Site Descriptionmentioning
confidence: 99%